Adhesive composition for dielectric layer, slurry composition for dielectric layer, dielectric layer, and laminated ceramic capacitor

By using a copolymer of cyano-containing monomers and (meth)acrylate monomers in a specific ratio as a binder, the cracking and adhesion problems of the dielectric layer in multilayer ceramic capacitors were solved, improving crack resistance and lamination performance, and promoting efficient production and transferability of the dielectric layer.

CN120957959APending Publication Date: 2025-11-14ZEON CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480023055.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-11
Filing Date
2024-08-14
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Existing technologies for manufacturing multilayer ceramic capacitors struggle to effectively suppress crack formation in the dielectric layer and improve lamination, resulting in poor adhesion of the dielectric layer.

Method used

A copolymer containing cyano monomer units and (meth)acrylate monomer units is used as a binder composition, and its content in the copolymer is controlled to be above 10% by mass and below 45% by mass. The glass transition temperature of the copolymer is controlled to be above -50°C and below 50°C. Particulate copolymers are used and the volume average particle size is above 0.01μm and below 0.5μm.

Benefits of technology

It improves the crack resistance and lamination properties of the dielectric layer, ensuring that the dielectric layer does not remain on the release substrate during peeling, and also improves the transferability of the dielectric layer, thus promoting the efficient production of laminated ceramic capacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120957959A_ABST
    Figure CN120957959A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide an adhesive composition for a dielectric layer, which is capable of imparting excellent crack resistance and lamination properties to the dielectric layer. This adhesive composition for a dielectric layer contains a copolymer that contains a cyano-group-containing monomer unit and a (meth) acrylic acid ester monomer unit, and the content ratio of the cyano-group-containing monomer unit is from 10% by mass to 45% by mass (inclusive) when all repeating units contained in the copolymer are 100% by mass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to adhesive compositions for dielectric layers, paste compositions for dielectric layers, dielectric layers, and multilayer ceramic capacitors. Background Technology

[0002] Multilayer ceramic capacitors are typically manufactured using dielectric layers such as ceramic green sheets.

[0003] The aforementioned dielectric layer can be obtained, for example, by preparing a slurry composition comprising a binder, a dielectric material, and a solvent, then applying the slurry composition onto a release substrate, followed by drying. The resulting dielectric layers can then be overlapped, arbitrarily degreased (binder removal treatment), and sintered to obtain a multilayer ceramic capacitor.

[0004] In recent years, in order to endow multilayer ceramic capacitors with excellent properties, the development of binders contained in the paste compositions used to manufacture the dielectric layer has been continuously advanced.

[0005] For example, in Patent Document 1, as a binder for manufacturing ceramic green sheets, a binder with excellent thermal decomposition properties that can produce ceramic green sheets is proposed. The binder includes a binder resin composition that can achieve high porosity in ceramic green sheets and is less prone to defects such as cracks during the manufacture of sintered bodies. The binder resin composition has a specified gel fraction and contains a specified composite resin.

[0006] Existing technical documents

[0007] Patent documents

[0008] Patent document 1: Japanese Patent Application Publication No. 2018-165230. Summary of the Invention

[0009] The problem the invention aims to solve

[0010] In this regard, further improvements are required in the aspect of suppressing crack formation during the manufacture of sintered bodies (hereinafter sometimes referred to as "crack resistance") in dielectric layers such as ceramic green sheets.

[0011] Furthermore, in the manufacture of multilayer ceramic capacitors, dielectric layers are typically overlapped and pressurized to obtain a laminate, with the desired good adhesion between the dielectric layers (hereinafter sometimes referred to as "laminarity").

[0012] Therefore, the object of the present invention is to provide a binder composition for dielectric layers that can impart excellent crack resistance and lamination properties to the dielectric layer.

[0013] Furthermore, the present invention aims to provide a slurry composition for dielectric layers that can impart excellent crack resistance and lamination properties to the dielectric layer.

[0014] Furthermore, the present invention aims to provide a dielectric layer with excellent crack resistance and lamination properties.

[0015] Furthermore, the present invention aims to provide a multilayer ceramic capacitor formed by sintering a multilayer body formed by overlapping the above-mentioned dielectric layers.

[0016] Solution for solving the problem

[0017] The inventors conducted in-depth research to solve the above-mentioned problems. Then, the inventors made a new discovery that if the binder composition for the dielectric layer contains a copolymer containing cyano monomer units and (meth)acrylate monomer units, and the proportion of cyano monomer units is within a specified range, the above-mentioned problems can be solved, thereby completing the present invention.

[0018] That is, the present invention aims to effectively solve the above problems. [1] The present invention is an adhesive composition for dielectric layer, which comprises a copolymer containing cyano monomer units and (meth)acrylate monomer units, wherein the proportion of the cyano monomer units is 10% or more and 45% or less when all repeating units contained in the copolymer are 100% by mass.

[0019] If the binder composition for the dielectric layer is as described above, it can impart excellent crack resistance and lamination properties to the dielectric layer.

[0020] Furthermore, in the manufacture of multilayer ceramic capacitors, for example, after overlapping the dielectric layer with other layers and applying pressure, the dielectric layer can be peeled off from the release substrate. As a result, if the adhesive composition for the dielectric layer is as described above, it is possible to prevent the dielectric layer from remaining on the release substrate during peeling. In other words, if the adhesive composition for the dielectric layer is as described above, it can impart excellent transferability to the dielectric layer.

[0021] In this specification, "(meth)acrylic acid" refers to acrylic acid and / or methacrylic acid.

[0022] In this specification, the content ratio of various repeating units (monomer units) in the (co)polymer can be used as a reference. 1 Measured by nuclear magnetic resonance (NMR) methods such as H-NMR.

[0023] [2] In the above-mentioned [1] adhesive composition for dielectric layer, the glass transition temperature of the copolymer is preferably -50°C or higher and 50°C or lower.

[0024] If the glass transition temperature of the copolymer is above the lower limit mentioned above, the crack resistance of the resulting dielectric layer can be improved.

[0025] On the other hand, if the glass transition temperature of the copolymer is below the above-mentioned upper limit, the lamination and transferability of the resulting dielectric layer can be improved.

[0026] In this specification, the glass transition temperature of the copolymer can be determined according to the method described in the examples.

[0027] [3] In the above-mentioned [1] or [2] adhesive composition for dielectric layer, the copolymer is preferably a particulate copolymer.

[0028] If the copolymer is a particulate copolymer, the lamination properties of the resulting dielectric layer can be improved.

[0029] [4] In the above-mentioned [3] binder composition for dielectric layer, the volume average particle size of the above-mentioned particulate copolymer is preferably 0.01 μm or more and 0.5 μm or less.

[0030] If the volume average particle size of the particulate copolymer is above the lower limit mentioned above, the crack resistance of the resulting dielectric layer can be improved.

[0031] On the other hand, if the volume average particle size of the particulate copolymer is below the above-mentioned upper limit, the lamination and transferability of the resulting dielectric layer can be improved.

[0032] In this specification, the volume average particle size of the particulate copolymer refers to the particle size at which the cumulative volume calculated from the smallest particle size side of the particle size distribution (volume basis) obtained by laser diffraction is 50%, and can be determined according to the method described in the examples.

[0033] [5] In any of the above-mentioned [1] to [4] adhesive compositions for dielectric layers, the content of the above-mentioned (meth)acrylate monomer units is preferably 55% by mass or more and 90% by mass or less when all repeating units contained in the above-mentioned copolymer are 100% by mass.

[0034] If the content of (meth)acrylate monomer units is above the lower limit mentioned above, the lamination and transferability of the resulting dielectric layer can be improved.

[0035] On the other hand, if the content of (meth)acrylate monomer units is below the above-mentioned upper limit, the crack resistance of the resulting dielectric layer can be improved.

[0036] In addition, the present invention aims to effectively solve the above problems. [6] The present invention is a slurry composition for dielectric layer, which comprises the binder composition for dielectric layer, dielectric material and solvent described in any one of [1] to [5] above.

[0037] If the dielectric layer paste composition is as described above, it can impart excellent crack resistance and lamination properties to the dielectric layer.

[0038] Furthermore, if the dielectric layer paste composition is as described above, it can impart excellent transferability to the dielectric layer.

[0039] [7] In the slurry composition described above [6], the solvent is preferably water.

[0040] Using water as the solvent reduces the environmental impact. Furthermore, using water improves safety and ease of access.

[0041] Furthermore, the present invention aims to effectively solve the above-mentioned problems. [8] The present invention is a dielectric layer, which is formed by drying a coating film formed from the dielectric layer slurry composition described above [6] or [7].

[0042] The aforementioned dielectric layer exhibits excellent crack resistance and lamination properties.

[0043] Furthermore, the aforementioned dielectric layer is easy to process due to its excellent transferability, resulting in the efficient production of multilayer ceramic capacitors.

[0044] In addition, the present invention aims to effectively solve the above problems. [9] The present invention is a multilayer ceramic capacitor, which is formed by sintering a multilayer body formed by overlapping the dielectric layers described above [8].

[0045] The aforementioned multilayer ceramic capacitors exhibit excellent performance due to the use of dielectric layers with superior crack resistance and lamination properties.

[0046] Furthermore, the aforementioned multilayer ceramic capacitors exhibit excellent production efficiency due to the use of easily handled dielectric layers.

[0047] Invention Effects

[0048] According to the present invention, it is possible to provide a binder composition for dielectric layers that can impart excellent crack resistance and lamination properties to the dielectric layer.

[0049] Furthermore, according to the present invention, it is possible to provide a slurry composition for a dielectric layer that imparts excellent crack resistance and lamination properties to the dielectric layer.

[0050] Furthermore, according to the present invention, a dielectric layer with excellent crack resistance and lamination properties can be provided.

[0051] Furthermore, according to the present invention, it is possible to provide a multilayer ceramic capacitor formed by sintering a multilayer body formed by overlapping the above-mentioned dielectric layers. Attached Figure Description

[0052] Figure 1 This is a schematic cross-sectional view showing an example of a multilayer ceramic capacitor according to the present invention. Detailed Implementation

[0053] The embodiments of the present invention are described in detail below.

[0054] Here, the binder composition for the dielectric layer of the present invention (hereinafter sometimes simply referred to as the "binder composition") can be used to prepare the slurry composition for the dielectric layer of the present invention (hereinafter sometimes simply referred to as the "slurry composition"). Furthermore, the slurry composition of the present invention can be used to form a dielectric layer used in manufacturing multilayer ceramic capacitors, etc. Moreover, the dielectric layer of the present invention is formed by drying a coating film formed from the slurry composition of the present invention. In addition, the multilayer ceramic capacitor of the present invention is formed by overlapping dielectric layers formed using the slurry composition of the present invention and sintering the resulting laminate.

[0055] (Adhesive composition for dielectric layer)

[0056] The adhesive composition for dielectric layers of the present invention comprises a copolymer containing cyano-containing monomer units and (meth)acrylate monomer units, and optionally includes a solvent. Furthermore, the adhesive composition of the present invention may optionally further comprise components other than the copolymer and the solvent (hereinafter sometimes referred to as "other components"). Moreover, in the adhesive composition of the present invention, the proportion of cyano-containing monomer units is 10% by mass or more and 45% by mass or less when the total number of repeating units (total monomer units) contained in the copolymer is 100% by mass.

[0057] If the binder composition is as described above, it can impart excellent crack resistance and lamination properties to the dielectric layer. The reason for this is presumably that by including a specific ratio of cyano-containing monomer units and (meth)acrylate monomer units in the copolymer contained in the binder composition, the durability of the dielectric layer during sintering and the adhesion between the dielectric layers can be effectively improved simultaneously.

[0058] Furthermore, if the adhesive composition is as described above, it can impart excellent transferability to the dielectric layer.

[0059] In addition, the adhesive compositions described herein generally do not contain the dielectric materials described later.

[0060] <Copolymer>

[0061] The adhesive composition of the present invention comprises copolymers that function as adhesive materials, containing specific proportions of cyano-containing monomer units and (meth)acrylate monomer units, and optionally further containing monomer units other than cyano-containing monomer units and (meth)acrylate monomer units (hereinafter sometimes referred to as "other monomer units").

[0062] <<Cyano-containing monomer units>>

[0063] A cyano-containing monomer unit refers to a monomer unit that can be formed from a cyano-containing monomer. Examples of cyano-containing monomers include: acrylonitrile; methyl acrylonitrile, α-ethyl acrylonitrile, and other α-alkyl acrylonitriles; etc. These can be used alone or in combination of two or more in any proportion.

[0064] Among them, acrylonitrile and methacrylonitrile are preferred as cyano-containing monomers, and acrylonitrile is more preferred. That is, the copolymer preferably contains at least one of acrylonitrile units and methacrylonitrile units, and more preferably contains acrylonitrile units.

[0065] The proportion of cyano-containing monomer units should be 10% or more, preferably 15% or more, and preferably 45% or less, preferably 30% or less, and more preferably 25% or less, when the total repeating units (total monomer units) contained in the copolymer are 100% by mass.

[0066] If the proportion of cyano-containing monomer units is above the lower limit mentioned above, the crack resistance of the resulting dielectric layer can be improved.

[0067] On the other hand, if the proportion of cyano-containing monomer units is below the above-mentioned upper limit, the lamination and transferability of the resulting dielectric layer can be improved.

[0068] <<(meth)acrylate monomer unit>>

[0069] (Meth)acrylate monomer units refer to monomer units that can be formed from (meth)acrylate monomers. Examples of (meth)acrylate monomers include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, tert-butyl methacrylate, amyl methacrylate, hexyl methacrylate, heptyl methacrylate, 2-ethylhexyl methacrylate, octyl methacrylate, and alkyl methacrylates. These can be used individually or in combination.

[0070] Among these, ethyl (meth)acrylate, n-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate are preferred monomers, and ethyl acrylate, n-butyl acrylate, and 2-ethylhexyl acrylate are more preferred monomers. That is, the copolymer preferably contains at least one monomer unit selected from the group consisting of ethyl (meth)acrylate, n-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate units, and more preferably contains at least one monomer unit selected from the group consisting of ethyl acrylate, n-butyl acrylate, and 2-ethylhexyl acrylate units.

[0071] In addition, in this specification, "(meth)acrylate" refers to acrylate and / or methacrylate.

[0072] The content of (meth)acrylate monomer units is preferably 55% by mass or more, more preferably 70% by mass or more, even more preferably 75% by mass or more, and preferably 90% by mass or less, preferably 85% by mass or less, when the total number of repeating units (total monomer units) in the copolymer is 100% by mass.

[0073] If the content of (meth)acrylate monomer units is above the lower limit mentioned above, the lamination and transferability of the resulting dielectric layer can be improved.

[0074] On the other hand, if the content of (meth)acrylate monomer units is below the above-mentioned upper limit, the crack resistance of the resulting dielectric layer can be improved.

[0075] <<Other Monomer Units>>

[0076] Other monomer units refer to monomer units that can be formed from other monomers. There are no particular restrictions on other monomers as long as they are copolymerizable with the aforementioned monomers. Examples of other monomer units include, for instance, monomer units containing acid groups.

[0077] An acid-containing monomer unit refers to a monomer unit that can be formed from an acid-containing monomer. Examples of acid-containing monomers include those containing carboxylic acid groups and those containing sulfonic acid groups.

[0078] Examples of monomers containing carboxylic acid groups include monocarboxylic acids and their derivatives, dicarboxylic acids and their anhydrides, and their derivatives.

[0079] Examples of monocarboxylic acids include acrylic acid, methacrylic acid, and crotonic acid.

[0080] Examples of monocarboxylic acid derivatives include 2-ethylacrylic acid, isocrotonic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid, and α-chloro-β-E-methoxyacrylic acid.

[0081] Examples of dicarboxylic acids include maleic acid, fumaric acid, and itaconic acid.

[0082] As dicarboxylic acid derivatives, examples include methylmaleic acid, dimethylmaleic acid, phenylmaleic acid, chloromaleic acid, dichloromaleic acid, fluoromaleic acid, butyl maleate, nonyl maleate, decyl maleate, dodecyl maleate, octadecyl maleate, fluoroalkyl maleate, and other maleic acid monoesters.

[0083] Examples of anhydrides that are dicarboxylic acids include maleic anhydride, acrylic anhydride, methylmaleic anhydride, dimethylmaleic anhydride, and citrate anhydride.

[0084] In addition, acid anhydrides that generate carboxylic acid groups through hydrolysis can also be used as monomers containing carboxylic acid groups.

[0085] Furthermore, as a monomer containing a carboxylic acid group, olefinic unsaturated polycarboxylic acids such as butene tricarboxylic acid, olefinic unsaturated polycarboxylic acids such as monobutyl fumarate and mono-2-hydroxypropyl maleate, etc., can also be used.

[0086] Examples of monomers containing sulfonic acid groups include vinyl sulfonic acid, methyl vinyl sulfonic acid, (methyl) allyl sulfonic acid, and 3-allyloxy-2-hydroxypropanesulfonic acid.

[0087] In this specification, "(methyl)allyl" refers to allyl and / or methylallyl.

[0088] In one embodiment, acrylic acid, methacrylic acid, itaconic acid, and vinyl sulfonic acid are preferred as the acid-containing monomer. That is, when the copolymer contains acid-containing monomer units, the acid-containing monomer units are preferably selected from at least one of acrylic acid units, methacrylic acid units, itaconic acid units, and vinyl sulfonic acid units.

[0089] When the proportion of acid-containing monomer units is 100% by mass, it is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, more preferably 10% by mass or less, and more preferably 5% by mass or less.

[0090] If the proportion of acid-containing monomer units is above the lower limit mentioned above, the dispersion stability of copolymers in the binder composition and slurry composition can be improved.

[0091] On the other hand, if the proportion of acid-containing monomer units is below the above-mentioned upper limit, the anti-adhesion of the resulting dielectric layer can be improved.

[0092] <<Properties of Copolymers>>

[0093] The glass transition temperature of the copolymer is preferably above -50°C, more preferably above -45°C, more preferably below 50°C, and more preferably below 10°C.

[0094] If the glass transition temperature of the copolymer is above the lower limit mentioned above, the crack resistance of the resulting dielectric layer can be improved.

[0095] On the other hand, if the glass transition temperature of the copolymer is below the above-mentioned upper limit, the lamination and transferability of the resulting dielectric layer can be improved.

[0096] The copolymer contained in the binder composition of the present invention is preferably a particulate copolymer. If the copolymer is a particulate copolymer, the lamination properties of the resulting dielectric layer can be improved.

[0097] The copolymer contained in the adhesive composition of the present invention is preferably non-water-soluble. Here, in this specification, "non-water-soluble" means that when 0.5g of the copolymer is dissolved in 100g of water at a temperature of 25°C, the insoluble component is 90% or more by mass.

[0098] In the binder composition of the present invention, when the copolymer is a particulate copolymer, the average particle size of the particulate copolymer is preferably 0.01 μm or more, more preferably 0.1 μm or more, more preferably 0.5 μm or less, and more preferably 0.3 μm or less.

[0099] If the volume average particle size of the particulate copolymer is above the lower limit mentioned above, the crack resistance of the resulting dielectric layer can be improved.

[0100] On the other hand, if the volume average particle size of the particulate copolymer is below the above-mentioned upper limit, the lamination and transferability of the resulting dielectric layer can be improved.

[0101] <<Polymerization Methods of Copolymers>>

[0102] There are no particular restrictions on the polymerization method of the copolymer; any method such as solution polymerization, suspension polymerization, bulk polymerization, or emulsion polymerization can be used. Furthermore, addition polymerization such as ionic polymerization, free radical polymerization, and living radical polymerization can be employed as the polymerization reaction. Moreover, the polymerization solvents, emulsifiers, dispersants, polymerization initiators, chain transfer agents, and other additives used in the polymerization can be conventional substances, and their amounts can also be conventionally used.

[0103] <Solvent>

[0104] The solvents optionally included in the adhesive composition of the present invention are not particularly limited and can be any of water and organic solvents. As organic solvents, aqueous solvents such as methanol, ethanol, and isopropanol, as well as non-aqueous solvents such as methylbenzene (toluene) and xylene can be used.

[0105] In addition, the solvent optionally included in the adhesive composition of the present invention is preferably water, considering the reduction of environmental impact, safety and ease of availability.

[0106] <Other Ingredients>

[0107] The adhesive composition of the present invention may optionally contain other components. Examples of such other components include, for instance, the additives described above used in the polymerization of copolymers.

[0108] <Concentration of solid components in the adhesive composition for dielectric layers>

[0109] The concentration of solid components in the adhesive composition is preferably 20% by mass or more, more preferably 30% by mass or more, more preferably 60% by mass or less, and more preferably 50% by mass or less.

[0110] <Preparation Method of Adhesive Composition for Dielectric Layer>

[0111] The binder composition of the present invention can be prepared by mixing the above-described copolymer, along with optional solvents and other components, using known methods. Specifically, the binder composition can be prepared by mixing the above-described components using a ball mill, sand mill, bead mill, pigment disperser, sand mixer, ultrasonic disperser, homogenizer, planetary mixer, FILMICS, or a rotation-revolutionary mixer.

[0112] (Paste composition for dielectric layer)

[0113] The slurry composition for dielectric layers of the present invention comprises the binder composition, dielectric material, and solvent described above, and optionally includes a water-soluble polymer. Furthermore, the slurry composition of the present invention may further comprise components other than the copolymer, solvent, dielectric material, and water-soluble polymer (hereinafter sometimes referred to as "other components"). Here, when the binder composition contains a solvent, the solvent contained in the slurry composition may be entirely derived from the binder composition, or it may be a solvent newly added to the slurry composition in addition to the solvent derived from the binder composition. Moreover, because the slurry composition of the present invention contains the binder composition of the present invention, it can impart excellent crack resistance and lamination properties to the dielectric layer. Furthermore, because the slurry composition of the present invention contains the binder composition of the present invention, it can impart excellent transferability to the dielectric layer.

[0114] <Dielectric Materials>

[0115] As a dielectric material, there are no particular restrictions on any material with dielectric properties, but ceramic materials are preferred. Examples of ceramic materials include zirconium oxide, aluminum silicate, titanium oxide, zinc oxide, barium titanate, calcium zirconate, calcium titanate, strontium titanate, magnesium oxide, silane, magnesium aluminum spinel, silicon carbide, silicon nitride, and aluminum nitride. These ceramic materials can be used individually or in combination of two or more.

[0116] Here, as ceramic materials, ceramic materials with a perovskite structure whose main phase is represented by the general formula ABO3 are preferred. Examples of such ceramic materials include barium titanate (BaTiO3), calcium zirconate (CaZrO3), calcium titanate (CaTiO3), strontium titanate (SrTiO3), and Ba, which form a perovskite structure. 1-x-y Ca x Sr y Ti 1-z Zr zO3 (0≤x≤1, 0≤y≤1, 0≤z≤1), etc. Among them, barium titanate is preferred as a ceramic material with a perovskite structure as the main phase.

[0117] The volume average particle size of the dielectric material is preferably 0.01 μm or more, more preferably 0.02 μm or more, even more preferably 0.05 μm or more, even more preferably 0.08 μm or more, preferably 1 μm or less, more preferably 0.8 μm or less, even more preferably 0.5 μm or less, even more preferably 0.3 μm or less, and even more preferably 0.2 μm or less.

[0118] If the volume average particle size of the dielectric material is within the above-mentioned range, the dispersion stability of the dielectric material in the slurry composition can be improved. Moreover, a dielectric layer with uniformly dispersed dielectric material can be produced as a result.

[0119] In this specification, the volume-average particle size of a dielectric material refers to the particle size at which the cumulative volume calculated from the smallest particle size side of the particle size distribution (volume reference) obtained by laser diffraction is 50%.

[0120] When the total components (including solvents) in the slurry composition are 100% by mass, the proportion of dielectric material is preferably 40% by mass or more, more preferably 50% by mass or more, more preferably 80% by mass or less, and more preferably 70% by mass or less.

[0121] <Solvent>

[0122] The solvents contained in the slurry composition of the present invention may be the same solvents described in the "Solvent" section of the "Dielectric Layer Adhesive Composition" above.

[0123] Furthermore, from the perspective of reducing environmental impact, safety, and ease of acquisition, the solvent contained in the slurry composition of the present invention is preferably water.

[0124] <Water-soluble polymers>

[0125] The slurry composition of the present invention may optionally include a water-soluble polymer that functions as a viscosity modifier and a binder. There are no particular limitations on the water-soluble polymer, but it is preferred to contain structural units having hydroxyl groups.

[0126] Here, a structural unit having a hydroxyl group (hereinafter sometimes referred to as a "hydroxyl-containing structural unit") can be a structural unit that can be formed from a monomer having a hydroxyl group (hereinafter sometimes referred to as a "hydroxyl-containing monomer"), or it can be a structural unit that, after obtaining a polymer using a monomer composition containing a monomer having a specified functional group, modifies or converts that functional group into a hydroxyl group.

[0127] The structure of the hydroxyl-containing structural unit is not particularly limited as long as it is a repeating unit with a hydroxyl group. Furthermore, methods for introducing hydroxyl-containing structural units into water-soluble polymers include, for example, the following (1) or (2):

[0128] (1) A method for preparing a water-soluble polymer containing hydroxyl-containing structural units from a monomer composition containing hydroxyl-containing monomers;

[0129] (2) A method for preparing a polymer from a monomer composition containing a vinyl carboxylate monomer of the general formula: R-CO-O-CH=CH2 (where R is any structure, preferably an alkyl group with 1 or more carbon atoms and 19 or less), and saponifying the polymer to convert all or part of the “R-CO-O-” in the vinyl carboxylate monomer unit into hydroxyl groups, thereby preparing a water-soluble polymer containing vinyl alcohol units and optionally containing vinyl carboxylate monomer units.

[0130] Examples of hydroxyl-containing monomers used in the above (1) method include: olefinic unsaturated alcohols such as (meth)allyl alcohol, 3-buten-1-ol, and 5-hexen-1-ol; alkyl alcohol esters of olefinic unsaturated carboxylic acids such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, di-2-hydroxyethyl maleate, di-4-hydroxybutyl maleate, and di-2-hydroxypropyl itaconic acid; general formula: CH2=CR 1 -COO-(C q H 2q O) p-H (where p represents an integer from 2 to 9, q represents an integer from 2 to 4, and R1 represents hydrogen or methyl) represents esters of polyalkylene glycols and (meth)acrylic acid; mono(meth)acrylates of dihydroxy esters of dicarboxylic acids such as 2-hydroxyethyl-2'-(meth)acryloyloxyphthalate and 2-hydroxyethyl-2'-(meth)acryloyloxysuccinate; vinyl ethers such as 2-hydroxyethyl vinyl ether and 2-hydroxypropyl vinyl ether; (meth)allyl-2-hydroxyethyl ether, (meth)allyl-2-hydroxypropyl ether, (meth)allyl-3-hydroxypropyl ether, (meth)allyl-2-hydroxybutyl ether, (meth)allyl-3-hydroxybutyl ether, (meth)allyl-4-hydroxybutyl ether, (meth)allyl-6-hydroxyhexyl Mono(methyl)allyl ethers of alkylene glycols such as alkylene ethers; polyoxyalkylene glycol mono(methyl)allyl ethers such as diethylene glycol mono(methyl)allyl ether and dipropylene glycol mono(methyl)allyl ether; halogenated and hydroxyl-substituted mono(methyl)allyl ethers of (poly)alkylene glycols such as glycerol mono(methyl)allyl ether, (methyl)allyl-2-chloro-3-hydroxypropyl ether, and (methyl)allyl-2-hydroxy-3-chloropropyl ether; mono(methyl)allyl ethers of polyvalent phenols such as eugenol and isoeugenol and their halogenated derivatives; (methyl)allyl sulfides of alkylene glycols such as (methyl)allyl-2-hydroxyethyl sulfide and (methyl)allyl-2-hydroxypropyl sulfide; 2-hydroxyethyl (methyl)acrylamide and N-hydroxymethylacrylamide; etc. These can be used alone or in combination of two or more.

[0131] Examples of vinyl carboxylic acid monomers used in method (2) above include vinyl acetate, vinyl propionate, vinyl butyrate, vinyl hexanoate, vinyl octanoate, vinyl decanoate, vinyl laurate, vinyl myristate, vinyl palmitate, and vinyl stearate. These can be used alone or in combination of two or more. Vinyl acetate is particularly preferred.

[0132] Here, when preparing a water-soluble polymer by the method described in (2) above, the hydroxyl groups of the resulting water-soluble polymer can be partially acetalized. Examples of such water-soluble polymers include polyvinyl butyral, which has hydroxyl groups acetalized with butyral. Alternatively, polyvinyl acetal, such as S-LEC BL-2H manufactured by Sekisui Chemicals Co., Ltd., can be used as an example.

[0133] When the content of water-soluble polymer in the slurry composition is 100 parts by weight, it is preferably 0.01 parts by weight or more, more preferably 0.1 parts by weight or more, even more preferably 1 part by weight or more, preferably 20 parts by weight or less, and more preferably 15 parts by weight or less.

[0134] <Other Ingredients>

[0135] Other components that may be included in the slurry composition of the present invention include those that are the same as those described in the "Other Components" section of the "Dielectric Layer Adhesive Composition" above.

[0136] <Solids concentration of the slurry composition for dielectric layers>

[0137] The concentration of solid components in the slurry composition is preferably 20% by mass or more, more preferably 25% by mass or more, more preferably 90% by mass or less, and more preferably 80% by mass or less.

[0138] <Content of copolymer>

[0139] The content of copolymer (solid component) in the slurry composition is preferably 1 part by mass or more, more preferably 2 parts by mass or more, more preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 7 parts by mass or less when the dielectric material in the slurry composition is 100 parts by mass.

[0140] <Preparation Method of Dielectric Layer Slurry Composition>

[0141] The above-described slurry composition can be prepared by mixing the above-described components using a known mixing method. As a mixer used for preparation, the apparatus listed in the above-described "Method for Preparing an Adhesive Composition for a Dielectric Layer" can be cited.

[0142] (Dielectric layer)

[0143] The dielectric layer of the present invention is formed by drying a coating film formed from the above-described slurry composition of the present invention. The dielectric layer of the present invention is typically a dried film obtained by partially or completely removing the solvent from a coating film formed from the slurry composition of the present invention. That is, the dielectric layer of the present invention comprises the above-described copolymer and dielectric material, and may optionally include solvents, water-soluble polymers, and other components.

[0144] Here, the dielectric layer of the present invention is formed by drying a coating film formed from the slurry composition of the present invention, thus exhibiting excellent crack resistance and lamination properties. Furthermore, the dielectric layer of the present invention is easy to process due to its excellent transferability, resulting in efficient production of multilayer ceramic capacitors.

[0145] When the total composition of the dielectric material in the dielectric layer is 100% by mass, the content of the dielectric material is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 85% by mass or more, preferably 98% by mass or less, and more preferably 95% by mass or less.

[0146] The content of the copolymer in the dielectric layer is preferably 1 part by mass or more, more preferably 2 parts by mass or more, more preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 7 parts by mass or less, when the dielectric material in the dielectric layer is 100 parts by mass.

[0147] When the dielectric layer contains a water-soluble polymer, the content of the water-soluble polymer in the dielectric layer is 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, even more preferably 1 part by mass or more, more preferably 20 parts by mass or less, and more preferably 15 parts by mass or less, when the dielectric material in the dielectric layer is 100 parts by mass.

[0148] The thickness of the dielectric layer is preferably 0.1 μm or more, more preferably 0.5 μm or more, more preferably 10 μm or less, and more preferably 5 μm or less.

[0149] The dielectric layer of the present invention can form a conductor layer on the dielectric layer. The conductor layer can be formed by various printing methods such as screen printing, gravure printing, embossing printing, inkjet printing, and offset printing using patterns formed by these methods, as well as vacuum evaporation for forming metal vapor deposition films.

[0150] Here, conductive paste can be used when forming the conductor layer by printing. The conductive paste can be prepared by existing known methods, for example, by mixing conductive powders such as metals, dispersants, plasticizers, solvents, etc., into polyvinyl alcohol acetal resin.

[0151] <Method for fabricating dielectric layers>

[0152] The dielectric layer can be made by applying the slurry composition of the present invention onto a release substrate and drying it to form a coating film.

[0153] Here, the release substrate used in fabricating the dielectric layer is preferably made of a flexible resin. By using a flexible resin as the release substrate, the release substrate (laminated film) on which the dielectric layer is formed, obtained by coating the release substrate with the slurry composition and drying, can be stored in a rolled state and supplied as needed.

[0154] There are no particular limitations on the release substrate, and examples include substrates containing polyesters such as polyethylene terephthalate and polyethylene naphthalate, polyethylene, polypropylene, polystyrene, polyimide, polyvinyl alcohol, and polyvinyl chloride.

[0155] The release substrate preferably undergoes a surface treatment to improve release properties on the side surface where the dielectric layer of the present invention is formed. There are no particular limitations on the surface treatment; examples include surface treatment using release agents such as silicone-based release agents, fluorine-based release agents, and wax-based release agents.

[0156] There are no particular restrictions on the thickness of the release substrate, which is usually above 20μm and below 100μm.

[0157] There are no particular limitations on the method of applying the slurry composition to the release substrate. Examples of known coating methods include various roller coating machines, such as those using a coater, a gravure coating machine, and a corner roller coating machine (registered trademark).

[0158] There are no particular limitations on the drying method for the coating film formed on the release substrate, and known drying methods such as using a hot air dryer can be cited as examples. In addition, the drying conditions can be appropriately set according to the solvent content in the coating film, the coating film thickness, etc. The drying temperature is usually above 80°C and below 150°C, and the drying time is usually above 3 minutes and below 60 minutes.

[0159] Furthermore, when the dielectric layer of the present invention is used to manufacture multilayer ceramic capacitors, multiple dielectric layers can be overlapped and then heat-pressed. The dielectric layer can be peeled off from the release substrate before or after the overlap and heat-pressing of the dielectric layers.

[0160] (Laminated ceramic capacitor)

[0161] The multilayer ceramic capacitor of the present invention is formed by sintering a laminate (sintered body) formed by overlapping the dielectric layers of the present invention described above. The multilayer ceramic capacitor of the present invention exhibits excellent performance due to the use of dielectric layers with excellent crack resistance and lamination properties. Furthermore, the multilayer ceramic capacitor of the present invention boasts excellent production efficiency due to the use of easily processed dielectric layers.

[0162] Additionally, the following references Figure 1 This describes one example of the multilayer ceramic capacitor of the present invention, but the multilayer ceramic capacitor of the present invention is not limited thereto.

[0163] Figure 1 This is a schematic cross-sectional view showing an example of a multilayer ceramic capacitor according to the present invention. Figure 1 The illustrated multilayer ceramic capacitor 10 has alternating layers of dielectric 11 and layered internal electrodes 12, and a pair of external electrodes 13 on the outside of the dielectric 11 and the internal electrodes 12. Furthermore, one of the pair of internal electrodes 12 adjacent to each other along the stacking direction, separated by the dielectric 11, is electrically connected to one of the pair of external electrodes 13 inside the multilayer ceramic capacitor 10, while the other of the pair of internal electrodes 12 adjacent to each other along the stacking direction is electrically connected to the other of the pair of external electrodes 13 inside the multilayer ceramic capacitor 10. Thus, a structure in which multiple capacitor elements are electrically connected in parallel is formed between the pair of external electrodes 13. In addition, the interfaces between the dielectric layers formed when the dielectric layers of the present invention are stacked can disappear due to the sintering process, thus... Figure 1 Not shown in the image.

[0164] There are no particular limitations on the multilayer ceramic capacitor, and it can be manufactured by existing known methods. For example, the multilayer ceramic capacitor can be manufactured by: overlapping multiple layers of the dielectric layer of the present invention, which forms a conductor layer that can serve as an internal electrode, in an alternating manner of dielectric and conductor layers; heating and pressing them together to form a laminate; thermally decomposing and removing the binder components (polymers, etc.) contained in the laminate (degreasing treatment); further sintering it; and then forming an external electrode on the end face of the sintered ceramic body.

[0165] Degreasing is typically carried out in a nitrogen atmosphere at a temperature above 300°C and below 500°C. The degreasing time is usually between 1 hour and 5 hours.

[0166] In addition, the content of the binder component in the degreased laminate is usually below 50 ppm.

[0167] Sintering of laminates after degreasing is typically performed at an oxygen partial pressure of 10. -9 ~10 -12 The sintering process is carried out in a reducing atmosphere such as H2-N2-H2O gas at a pressure of MPa at a temperature above 1000℃ and below 1500℃. The sintering time of the laminate is usually more than 1 hour and less than 30 hours.

[0168] External electrodes can be formed by coating the end face of a sintered ceramic body with an external electrode material and then firing it. This can yield, for example... Figure 1 The stacked ceramic capacitor shown.

[0169] Examples of materials used for external electrodes include Cu paste containing glass frit. Firing is typically performed in a nitrogen atmosphere at a temperature between 500°C and 1500°C. Alternatively, Ni, Sn, or other coatings can be applied to the surface of the external electrode.

[0170] [Example]

[0171] The present invention will be specifically described below based on embodiments, but the present invention is not limited to these embodiments. Furthermore, in the following description, unless otherwise specified, "%" and "parts" refer to quantities based on mass.

[0172] Furthermore, in polymers manufactured by polymerizing multiple monomers, the proportion of monomer units formed by the polymerization of a certain monomer in the polymer is usually consistent with the proportion of that monomer in all monomers used in the polymerization of the polymer (feed ratio), unless otherwise specified.

[0173] In addition, the volume average particle size, glass transition temperature, crack resistance, lamination and transferability of the copolymer were determined and evaluated according to the following steps.

[0174] <Method for determining the volume average particle size of copolymers>

[0175] The volume average particle size of the copolymers in the examples and comparative examples was determined by laser diffraction. Specifically, an aqueous dispersion containing the copolymer (with a solid content concentration adjusted to 0.1% by mass) was used as the sample. Then, in the particle size distribution (volume basis) measured using a laser diffraction particle size distribution measuring device (Beckman Coulter, product name "LS-230"), the particle size D50 at which the cumulative volume calculated from the small diameter side becomes 50% was taken as the volume average particle size.

[0176] In addition, in Example 6, since the copolymer was non-particulate, the volume average particle size was not measured.

[0177] <Method for determining the glass transition temperature of copolymers>

[0178] The copolymers (binder compositions) of the examples and comparative examples were dried for 3 days at 50% humidity and 25°C to obtain a film with a thickness of 1.0 mm. This film was then dried in a vacuum dryer at 60°C for 10 hours. Subsequently, using the dried film as a sample, the glass transition temperature (°C) was determined according to JIS K7121 at a measurement temperature of -100°C to 180°C and a heating rate of 5°C / min using a DSC6220SII (differential scanning calorimeter, NanoTechnology).

[0179] <Crack Resistance>

[0180] The dielectric layer (release substrate with dielectric layer) formed on the release substrate in the examples and comparative examples was cut into squares 5cm wide × 5cm long. The release substrate was then peeled off to obtain test pieces. Two test pieces were prepared, overlapped, and subjected to a temperature of 80°C and 5kg / cm². 2 Press under pressure for 60 seconds. Then, fire at 1000°C for 5 hours and then at 1200°C for 5 hours. Visually inspect the dielectric layer and evaluate crack resistance according to the following criteria.

[0181] A: No cracks were produced at 1000℃ and 1200℃.

[0182] B: No cracks appeared at 1000℃, but cracks appeared at 1200℃.

[0183] C: Cracks appeared at both 1000℃ and 1200℃.

[0184] <Layering>

[0185] The release substrate with the dielectric layer manufactured in the examples and comparative examples was cut into squares 5cm wide × 5cm long. The release substrate was then peeled off to obtain test pieces. Two test pieces were prepared, overlapped, and subjected to a temperature of 80°C and 5kg / cm². 2 Press under pressure for 60 seconds. Afterward, cut the overlapping dielectric layers with a tool, visually confirm the cross-section of the overlapping dielectric layers, and evaluate the lamination according to the following criteria.

[0186] A: The dielectric layers are bonded together, and there is no powder or debris falling off the cut surface.

[0187] B: The dielectric layers are bonded together, but powder particles are falling off at the cut surface.

[0188] C: The dielectric layers were not bonded together, and powder debris was found on the cut surface.

[0189] <Transferability>

[0190] The release substrates with dielectric layers manufactured in the examples and comparative examples were cut into squares 5 cm wide × 5 cm long as test pieces. Two test pieces were prepared and overlapped with the dielectric layers facing each other, and pressed for 10 seconds at 40°C and 5 kg / cm². Afterward, the release substrate of one test piece was peeled off, and the peeling state (transferability) of the dielectric layer was visually confirmed. The transferability was evaluated according to the following criteria.

[0191] A: The dielectric layers remain bonded together, and no dielectric layer residue remains on the surface of the peeled-off release substrate.

[0192] B: The dielectric layers remain bonded together, but some dielectric layer residue remains on the surface of the peeled-off release substrate.

[0193] C: The dielectric layers are not bonded together, and most of the dielectric layer remains on the surface of the release substrate.

[0194] (Example 1)

[0195] <Preparation of Aqueous Dispersions of Copolymers (Binder Compositions)>

[0196] In polymerization reactor A, 74 parts of deionized water, 0.2 parts of sodium dodecyl diphenyl ether sulfonate, and 1.0 part of ammonium persulfate as a polymerization initiator were added. The mixture was heated to 70°C and stirred for 30 minutes. Next, in another polymerization reactor B, 78.0 parts of 2-ethylhexyl acrylate as a (meth)acrylate monomer, 20.0 parts of acrylonitrile as a cyano-containing monomer, 2.0 parts of itaconic acid as another monomer (acid-containing monomer), 0.8 parts of sodium dodecyl diphenyl ether sulfonate as an emulsifier, and 74 parts of deionized water were added and stirred to prepare an emulsion. The prepared emulsion was added sequentially from polymerization reactor B to polymerization reactor A over approximately 200 minutes. The resulting mixture was stirred for approximately 180 minutes, and the reaction was terminated by cooling when the monomer conversion reached 97% or higher. Afterward, the pH was adjusted with a 4% sodium hydroxide aqueous solution, and unreacted monomers were removed by heated vacuum distillation to obtain an aqueous dispersion of the copolymer (binder composition). The pH of the obtained aqueous dispersion was 8.0. The glass transition temperature and volume average particle size of the copolymer were determined using the obtained aqueous dispersion. The results are shown in Table 1.

[0197] <Preparation of Slurry Composition>

[0198] 100 parts of barium titanate (manufactured by Sakai Chemical Industry Co., Ltd., "BT-01") with a volume average particle size (d50) of 0.1 μm as the dielectric material, 5 parts of polyvinyl butyral (manufactured by Sekisui Chemicals Co., Ltd., S-LEC BL-2H) as the water-soluble polymer (based on solids), and 20 parts of water as the solvent, along with 100 parts of zirconia beads (manufactured by Nichika Toyoda Co., Ltd.) with a particle size of 0.1 mm, were stirred at 500 rpm for 2 hours using a bead mill (manufactured by Aimex Co., Ltd., "RMB-01"). Then, 20 parts of water were added, and the mixture was stirred at 500 rpm for 1 hour. The zirconia beads were removed by filtration to prepare a dispersion of barium titanate. 5 parts of the obtained copolymer (12.5 parts as an aqueous dispersion) were added to 152.5 parts of this dispersion (100 parts of barium titanate content), and the mixture was stirred at 1000 rpm for 3 minutes using a rotary mixer to prepare a slurry composition.

[0199] <Fabrication of the Dielectric Layer>

[0200] The above-obtained slurry composition was applied using a gravure coating machine to a 100mm wide × 100mm long release-treated film (Lintec Co., Ltd., PET38AL-5) with a dielectric layer thickness of approximately 1.0 μm after drying. The film was then dried in an oven at 100°C for 5 minutes to obtain a dielectric layer on the release substrate (ceramic green sheet method). Crack resistance, lamination properties, and transferability were evaluated using the resulting release substrate with the dielectric layer. The results are shown in Table 1.

[0201] (Example 2)

[0202] In the preparation of the aqueous dispersion of the copolymer, the amount of 2-ethylhexyl acrylate was changed from 78.0 parts to 86.0 parts, and the amount of acrylonitrile was changed from 20.0 parts to 12.0 parts. The rest was the same as in Example 1. Various operations, measurements and evaluations were performed. The results are shown in Table 1.

[0203] (Example 3)

[0204] In the preparation of the aqueous dispersion of the copolymer, the amount of 2-ethylhexyl acrylate was changed from 78.0 parts to 70.0 parts, and the amount of acrylonitrile was changed from 20.0 parts to 28.0 parts. The rest was the same as in Example 1, and various operations, measurements and evaluations were performed. The results are shown in Table 1.

[0205] (Example 4)

[0206] In the preparation of the aqueous dispersion of the copolymer, the amount of sodium dodecyl diphenyl ether sulfonate added in polymerization reactor A was changed from 0.2 parts to 0.8 parts, and the amount of sodium dodecyl diphenyl ether sulfonate added in polymerization reactor B was changed from 0.8 parts to 1.0 parts. The rest was the same as in Example 1, and various operations, measurements and evaluations were performed. The results are shown in Table 1.

[0207] (Example 5)

[0208] In the preparation of the aqueous dispersion of the copolymer, sodium dodecyl diphenyl ether sulfonate was not added to polymerization reactor A. The amount of sodium dodecyl diphenyl ether sulfonate added to polymerization reactor B was changed from 0.8 parts to 0.5 parts. The rest was the same as in Example 1. Various operations, measurements and evaluations were performed. The results are shown in Table 1.

[0209] (Example 6)

[0210] As an aqueous dispersion of the copolymer, an aqueous solution of the copolymer obtained according to the following steps was used, with all other procedures being the same as in Example 1, for various operations, measurements, and evaluations. The results are shown in Table 1.

[0211] <Preparation of aqueous solutions of copolymers (binder compositions)>

[0212] In a 1L four-necked flask equipped with a reflux condenser, thermometer, air inlet tube, and stirrer, 78.0 parts of 2-ethylhexyl acrylate (as a (meth)acrylate monomer), 20.0 parts of acrylonitrile (as a cyano-containing monomer), 2.0 parts of itaconic acid (as another monomer, including acidic monomers), and 100 parts of water were added to prepare a mixture. While stirring the mixture, 2 parts of benzoyl peroxide (as a polymerization initiator) were added. The mixture was stirred continuously and heated to 80°C. After reaching 80°C, the mixture was stirred further at 80°C for 5 hours. Then, the temperature inside the flask was cooled to room temperature, and 10 parts of diethanolamine (as an amine component) were slowly added for neutralization. This yielded an aqueous solution of the copolymer (binder composition).

[0213] (Example 7)

[0214] In the preparation of the aqueous dispersion of the copolymer, 2-ethylhexyl acrylate was replaced with ethyl acrylate, and the rest was the same as in Example 1, with various operations, measurements and evaluations performed. The results are shown in Table 1.

[0215] (Example 8)

[0216] In the preparation of the aqueous dispersion of the copolymer, the amount of 2-ethylhexyl acrylate was changed from 78.0 parts to 80.0 parts, itaconic acid was not added, and the rest was the same as in Example 1. Various operations, measurements and evaluations were performed. The results are shown in Table 1.

[0217] (Comparative Example 1)

[0218] In the preparation of the aqueous dispersion of the copolymer, the amount of 2-ethylhexyl acrylate was changed from 78.0 parts to 90.0 parts, and the amount of acrylonitrile was changed from 20.0 parts to 8.0 parts. The rest was the same as in Example 1, and various operations, measurements and evaluations were performed. The results are shown in Table 1.

[0219] (Comparative Example 2)

[0220] In the preparation of the aqueous dispersion of the copolymer, the amount of 2-ethylhexyl acrylate was changed from 78.0 parts to 48.0 parts, and the amount of acrylonitrile was changed from 20.0 parts to 50.0 parts. The rest was the same as in Example 1, and various operations, measurements and evaluations were performed. The results are shown in Table 1.

[0221] Furthermore, in Table 1,

[0222] “AN” represents an acrylonitrile unit.

[0223] "2-EHA" represents the 2-ethylhexyl acrylate unit.

[0224] “EA” represents the ethyl acrylate unit.

[0225] “IA” represents the itaconic acid unit.

[0226] [Table 1]

[0227]

[0228] As can be seen from Table 1, the binder composition for dielectric layers according to the embodiments can impart excellent crack resistance and lamination properties to the dielectric layers.

[0229] Industrial availability

[0230] According to the present invention, it is possible to provide a binder composition for dielectric layers that can impart excellent crack resistance and lamination properties to the dielectric layer.

[0231] Furthermore, according to the present invention, it is possible to provide a slurry composition for a dielectric layer that imparts excellent crack resistance and lamination properties to the dielectric layer.

[0232] Furthermore, according to the present invention, a dielectric layer with excellent crack resistance and lamination properties can be provided.

[0233] Furthermore, according to the present invention, it is possible to provide a multilayer ceramic capacitor formed by sintering a multilayer body formed by overlapping the above-mentioned dielectric layers.

[0234] Explanation of reference numerals in the attached figures

[0235] 10: Multilayer ceramic capacitors

[0236] 11: Dielectric

[0237] 12: Internal electrodes

[0238] 13: External Electrode

Claims

1. An adhesive composition for a dielectric layer, comprising a copolymer, said copolymer containing cyano-containing monomer units and (meth)acrylate monomer units, The proportion of the cyano-containing monomer unit is 10% or more and 45% or less when all repeating units contained in the copolymer are 100% by mass.

2. The adhesive composition for dielectric layers according to claim 1, wherein, The copolymer has a glass transition temperature above -50°C and below 50°C.

3. The adhesive composition for dielectric layers according to claim 1, wherein, The copolymer is a particulate copolymer.

4. The adhesive composition for dielectric layers according to claim 3, wherein, The volume average particle size of the particulate copolymer is greater than 0.01 μm and less than 0.5 μm.

5. The adhesive composition for dielectric layers according to claim 1, wherein, The content of the (meth)acrylate monomer unit is 55% by mass or more and 90% by mass or less when all repeating units contained in the copolymer are 100% by mass.

6. A slurry composition for a dielectric layer, comprising the binder composition for a dielectric layer according to any one of claims 1 to 5, a dielectric material, and a solvent.

7. The slurry composition for a dielectric layer according to claim 6, wherein, The solvent is water.

8. A dielectric layer formed by drying a coating film made from the dielectric layer slurry composition of claim 6.

9. A multilayer ceramic capacitor, which is formed by sintering a multilayer of dielectric layers as described in claim 8.

Citation Information

Patent Citations

  • Binder for production of mineral sintered bodies

    JP2018165230A